How ubiquitous is ubiquitous communication? Assessing bandwidth distributions among 172 countries from 1986 to 2013 - Martin Hilbert (International Telecommunications Society (ITS), 2015)
Any assessment of ubiquitous, intelligent and mobile communication networks has to start with an adequate assessment of the underlying infrastructure. As the digital age continues its evolution into the new paradigms of big data and smart things, the digital divide evolves with it. While the analysis of digital deprivation traditionally has focused on the number of telecommunication subscriptions, the current evolution is adding new dimensions to the challenge of digital equality. While end-user subscriptions like phones and internet connections are reaching a certain level of saturation, the divide in terms of bandwidth continues to unfold its surprising dynamics. In order to obtain a better understanding of this dynamic, this study quantifies global digital development for 172 countries from 1986 to 2013 in terms of three indicators: the number of telecom subscriptions (phones, internet, tablets and wearables); the corresponding bandwidth (in kbps, fixed and mobile, upload and download); and the equality of the arising distribution among and within countries. It shows that the divide in terms of end-user subscriptions is rapidly closing, while the divide in terms of bandwidth is far from being closed and is instead being converted into a permanent structural characteristic of modern societies. The reason is that installed bandwidth potential in terms of kbps per capita is closely linked to income per capita, which is characterized by a notoriously persistent inequality. Novel findings reveal that only 3 countries host 50 % of the globally installed bandwidth potential (10 countries 75 %) and that the contribution of mobile access solutions to global bandwidth is continuously fluctuating with incessant technological innovation, reaching almost 40 % in both 2001 and 2013, while falling to 16 % in 2007. In terms of inequality, we show that the digital divide between high- and low income countries in terms of kbps per capita has increased between 2001 and 2008, only decreasing below historic levels very recently during 2012-2013. Nevertheless, it is constantly increasing in absolute terms. In 2003, the average inhabitant of high income countries had access to 90 kbps more than the average inhabitant of the rest of the world (100 vs. 10 kbps). This divide increased with an order of magnitude every 5 years, reaching almost 900 kbps in 2007, and over 10,000 kbps by 2013. This increasing divide in absolute terms is important to notice in the context of a big data world, in which the amount of data is becoming a crucial ingredient for growth and development. We also estimate the distribution of digital equality within countries by using a worst-case approximation method. It shows that national inequality has increased between 1995 and 2009, which is surprising, considering the habitual talk about ubiquitous communication networks in the digital age. Our Gini coefficient within countries decreases only very recently, during the past three years. This shows that the adjective 'ubiquitous' is finally starting to convert from a mere promise into a tangible and quantifiable opportunity.
Keywords: 330